2016
DOI: 10.7759/cureus.573
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cervical Discectomy and Fusion (ACDF): Comparison Between Zero Profile Implants and Anterior Cervical Plate and Spacer

Abstract: Introduction: Interposition grafts combined with anterior plating currently remain the gold standard for anterior cervical discectomy and fusion. The use of anterior plates increases fusion rates but may be associated with higher rates of postoperative dysphagia. The aim of the current study was to determine the clinical and radiological outcomes following anterior cervical discectomy and fusion (ACDF) using zero-profile anchored spacers versus standard interposition grafts with anterior plating.Methods: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…A large number of clinical studies have shown that after plate xation is xed, the plate will protrude from the surface of cervical body, which cause slight compression on the esophagus [17,18] . Some scholars reported that the use of thinner plate xation will reduce the incidence of dysphagia [19] . Previous studies have also shown that the use of zero-pro le anchored spacer can signi cantly reduce the incidence of dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of clinical studies have shown that after plate xation is xed, the plate will protrude from the surface of cervical body, which cause slight compression on the esophagus [17,18] . Some scholars reported that the use of thinner plate xation will reduce the incidence of dysphagia [19] . Previous studies have also shown that the use of zero-pro le anchored spacer can signi cantly reduce the incidence of dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…ACDF improved the modified JOA scores and Nurick grades postoperatively [13,14]. Moreover, several studies reported that this technique provided higher postoperative JOA scores [9,[15][16][17][18][19].…”
Section: Clinical Outcomementioning
confidence: 98%
“…The primary complications after ACDF with anterior plate are chronic dysphagia and prevertebral soft tissue swelling [13,22]. The mechanism for these complications are still not well understood; however, it is proposed that retraction during surgery, direct pressure to the esophagus by the anterior plate, and irritation of the surrounding soft tissues may contribute to the complications occurring post ACDF with anterior plate [13].…”
Section: Surgical Outcomementioning
confidence: 99%
See 2 more Smart Citations